Characterization of Sustainable Robotic Materials and Finite Element Analysis of Soft Actuators Under Biodegradation - Nagai, Toshiaki; Kurita, Ashitaka; Shintake, Jun (Frontiers in Robotics and AI, 2021)
Biodegradability is an important property for soft robots that makes them environmentally friendly. Many biodegradable materials have natural origins, and creating robots using these materials ensures sustainability. Hence, researchers have fabricated biodegradable soft actuators of various materials. During microbial degradation, the mechanical properties of biodegradable materials change; these cause changes in the behaviors of the actuators depending on the progression of degradation, where the outputs do not always remain the same against identical inputs. Therefore, to achieve appropriate operation with biodegradable soft actuators and robots, it is necessary to reflect the changes in the material properties in their design and control. However, there is a lack of insight on how biodegradable actuators change their actuation characteristics and how to identify them. In this study, we build and validate a framework that clarifies changes in the mechanical properties of biodegradable materials; further, it allows prediction of the actuation characteristics of degraded soft actuators through simulations incorporating the properties of the materials as functions of the degradation rates. As a biodegradable material, we use a mixture of gelatin and glycerol, which is fabricated in the form of a pneumatic soft actuator. The experimental results show that the actuation performance of the physical actuator reduces with the progression of biodegradation. The experimental data and simulations are in good agreement (R2 value up to 0.997), thus illustrating the applicability of our framework for designing and controlling biodegradable soft actuators and robots.